2021
DOI: 10.1182/blood.2020010150
|View full text |Cite
|
Sign up to set email alerts
|

Clonal hematopoiesis and therapy-related myeloid neoplasms following neuroblastoma treatment

Abstract: Syndrome (CAPS) Registry Project Group (European Forum on Antiphospholipid Antibodies). Relapsing catastrophic antiphospholipid syndrome potential role of microangiopathic hemolytic anemia in disease relapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Mutational signature analysis. Mutation signatures were fitted to the trinucleotide counts of single-nucleotide variants in the main clone and subclone of ALL (PD38257a) and AML (PD38257c) using the SigFit algorithm 51 and the COSMIC reference database of mutational signatures (https://cancer.sanger.ac.uk/signatures/ sbs/, v3.2), as used previously 52 . Initially, all reference signatures were fitted to the mutation counts.…”
Section: Focus | Articlesmentioning
confidence: 99%
“…Mutational signature analysis. Mutation signatures were fitted to the trinucleotide counts of single-nucleotide variants in the main clone and subclone of ALL (PD38257a) and AML (PD38257c) using the SigFit algorithm 51 and the COSMIC reference database of mutational signatures (https://cancer.sanger.ac.uk/signatures/ sbs/, v3.2), as used previously 52 . Initially, all reference signatures were fitted to the mutation counts.…”
Section: Focus | Articlesmentioning
confidence: 99%
“…t-MN comprises two disease types, namely, therapy-related acute myeloid leukemia (t-AML) and therapy-related myelodysplastic syndrome (t-MDS; refs. 15,16). In t-MN genomes, high numbers of clonal platinum-and thiopurine-induced mutations could be observed, which indicated that in these cases clonal expansion of the hematopoietic cell founding the leukemia started after the initiation of exposure (5).…”
Section: Introductionmentioning
confidence: 97%
“…Since BRCA mutations predispose patients to multiple cancer types that generally have an increased sensitivity to platinum-based agents, patients with g BRCA -associated HGOC are more likely to have undergone treatment with platinum and alkylating agents. Platinum chemotherapy specifically appears to cause clonal expansion that can lead to leukemia ( Coorens et al, 2021 ). The platinum effect is suggested by the difference in the observed rates of MDS/AML on PARPi in newly diagnosed vs. relapsed HGOC (<1.5% vs. 8%) and the 4% rate of MDS/AML in the placebo group with relapsed disease ( Poveda et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%